Analisis Rasio Keuangan Untuk Mengukur Kinerja Keuangan Pada PT.Pelabuhan Indonesia I (Persero) Periode 2013-2017 : (Berdasarkan Keputusan Menteri BUMN Nomor: KEP-100/MBU/2002) - Rosanna Purba; Renika Hasibuan; Prananda Akbar Syam (Owner : Riset dan Jurnal Akuntansi, 2021)
This study aims to determine and analyze the level of financial performance at PT. Pelabuhan Indonesia I (Persero) for the period 2013-2017 in terms of financial ratio analysis based on the Decree of the Minister of BUMN No: KEP-100/ MBU/2002. Information on the condition of the company's financial performance is necessary to maintain the company's existence from competition. The analytical method used is descriptive method with a quantitative approach, with data collection techniques in the form of documentation studies. The data analyzed were the financial statements of PT. Pelabuhan Indonesia I (Persero), which is the income statement and statement of financial position (balance sheet) for the period 2013-2017. Assessment of the performance level from the financial aspect based on the Decree of the Minister of BUMN No: KEP-100/MBU/2002 uses 8 (eight) financial ratio indicators, which is Return On Equity, Return On Investment, Cash Ratio, Current Ratio, Collection Periods, Inventory Turnover, Total Asset Turn Over, and the Ratio of Equity Capital to Total Assets. The results of the assessment of financial performance PT. Pelabuhan Indonesia I (Persero) received a healthy predicate with the AA category in a row during the period 2013 to 2017.